Effective writing in psychology : papers, posters,and presentations - Beins, Bernard; Beins, Agatha, 1976-; Beins, Agatha M. (Malden, MA : Wiley-Blackwell, 2012)
'Writing and communication skills are invaluable tools for both students and professionals in the field of psychology. The new edition of this successful text helps users to generate crisp scientific communication, offering clear guidelines on effective writing, and illustrating how to generate strong and compelling prose. The book aids students, writers, and speakers at all levels by guiding them at every stage of the process. In a practical and accessible way, the authors teach readers how to form concise, unambiguous arguments, document their sources, and render technical information clear and comprehensible. Incorporating the latest writing guidelines found in the sixth edition of the Publication Manual of the American Psychological Association, this new edition: Offers an understanding of why APA style is important. Includes a chapter on conducting a literature search, to guide students through databases, keywords, sources, and connections between articles. Offers tips on creating poster presentations, giving talks, writing for the Internet, and making presentations to institutional review boards (IRBs). Provides a separate section on how to communicate statistics. Incorporates a new section on using the Internet to present research papers'--
Machine generated contents note: Preface to the Second Edition -- Preface to the First Edition -- Writing in Psychology -- Part I. Organizing and Developing Your Ideas and Writing -- Formulating your Ideas -- Assessing Your Sources -- How to Conduct a Literature Search -- How to Read and Summarize a Journal Article -- Organizing a Paper -- Elements of Style -- Communicating Statistics -- Part II. Preparing APA Format Papers -- Writing a Thesis or a Term Paper -- The Introduction Section -- The Method Section -- The Results -- The Discussion Section -- References : Citations in the Text and the Reference List -- Final Touches : The Abstract and Formatting Details -- Part III. Communicating Beyond the Research Paper -- Creating Poster Presentations -- Giving Oral Presentations -- Presenting your Work on the Internet -- Submitting Your Plan to an Ethics Committee -- Appendix A : Example of APA-Style Manuscript with Common Errors -- Appendix B : Corrected APA-Style Manuscript -- References -- Subject -- Index -- Author Index -- Franz/Group Dynamics and Team Interventions -- Preface -- SECTION I : INTRODUCTION -- Introduction to Teams -- Methods of Assessing and Evaluating Team Functioning -- SECTION II : INPUTS -- Team Theories and Concepts -- Understanding Culture and Diversity -- Preparing the Environment for Teamwork -- SECTION III : PROCESSES -- Improving Small Group Communication and Trust -- Improving Creativity and Innovation -- Improving Problem Solving and Decision Making -- Understanding Cohesion and Collaboration -- Reducing Dysfunctional Conflict and Improving Cooperation -- Influence, Power, and Leadership -- Working in Virtual Teams -- SECTION IV : OUTPUTS -- Searching for Synergy : Creating a High-Performing Team -- Appendix : Improving Team MeetingsReferences.
Includes bibliographical references and index.
Keywords: Psychology -- Authorship